Production and purification of protein A in cultures of Staphylococcus aureus from cattle - Müller, Ernst Eckehardt; Brückler, Jörg; Schaeg, Werner; Blobel, Hans (Pesquisa Agropecuaria Brasileira, 2014)
Of 345 cultures of Staphlococcus aureus, crystal-violettyp A, from cattle, 341 (98.8%) were protein A-positive in the hemagglutination test, 182 (52.7%) in the Ouchterlony double immune diffusion test and 180 (52.2%) in the precipitin ring test. Protein A was produced by growing the staphylococci for 18 hours at 37°C in fermenters with respectivelly 15 l caseine-peptone broth. The staphylococci were sedimented by continuous-flow centrifugation at 73,700 x g, washed repeatedly in sterile 0.14M Nacl and extracted with formic acid to obtain protein A. Partial purification of protein A in the formic acid extract could be achieved by absorbing basic proteins without protein A-activity onto cellulose phosphate and subsequente affinity-chromatography with human y-globuline, faction II of Cohn. The final product had an isoelectric point at about pH 4.4, as shown by isolectric focussing.